Improvement in yield and quality of okra (Abelmoschus esculentus) through crop spacing, mulching and irrigation levels in arid regions - MEENA, ATMA RAM; NAROLIA, RAJEEV KUMAR; YADAV, PRAMOD KUMAR; LATA, KUMARI; MEENA, SIYARAM (The Indian Journal of Agricultural Sciences, 2024)
The field experiments were conducted during the rainy (kharif) seasons of 2018–19 and 2019–20 at College of Agriculture, Swami Keshwanand Rajasthan Agricultural University, Bikaner, Rajasthan to study the effect of crop spacing, mulching and irrigation levels on yield and quality of okra [Abelmoschus esculentus (L.) Moench]. Experiment was laid out in split plot design (SPD) with four irrigation levels [40, 60, 80 and 100% pan evaporation (PE)] in the main plot. Two crop geometries (normal sowing and paired row sowing) and three mulches (no mulch, straw and plastic mulch in black colour) were used in the sub-plot and sub-sub-plot, respectively. The study found that using 40% of PE for irrigation led to the shortest time to first flowering (41.72 days). However, the highest fruit yield, leaf area index (LAI), total soluble solids (TSS), protein content and cost-benefit ratio (B:C ratio) were achieved when irrigating at 100% PE followed by 80% PE. Water use efficiency (WUE) was highest (17.24 kg/ha/mm) at 40% PE irrigation level. The highest fruit yield of 153.1 g/plant and 122.4 q/ha was achieved when straw mulch was applied. Considering the combined data, it’s worth mentioning that the B:C ratio was significantly greater when utilizing 100 PE irrigation without mulch. Conversely, WUE at 19.1 kg/ha/mm, showed a significant increase when employing 40% PE irrigation along with straw mulch. Therefore, the study demonstrates that utilizing paired row sowing with straw mulch and irrigation at 100% PE resulted in the highest growth attributes, fruit quality of okra and B:C ratio.